(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
This article focuses on the historical development of linguo-pragmatic analysis, focusing on its pragmatics and sociolinguistic foundations. He discusses key theories and methodologies, highlighting how this approach reveals hidden meanings and how language influences communication. Also, the article presents examples of practical application of linguopragmatic analysis in various linguistic studies.